A Comparative Study of the Brazilian Energy Labelling System and the Passivhaus Standard for Housing - Renata C. S. Tubelo; Lucelia T. Rodrigues; Mark Gillott (Buildings, 2014)
The ever-increasing energy demand of the residential sector has required the adoption of tighter energy standards, aiming for high energy efficiency in dwellings. In Brazil, 24 million new residential buildings are planned to be delivered by 2022 through social housing programs, which could greatly impact on the country’s energy consumption. In an attempt to minimize this impact, the Brazilian Labelling Scheme for Residential Buildings (RTQ-R label) was launched in 2010 as a voluntary standard for the evaluation of housing energy efficiency. The RTQ-R label focuses on building fabric and hot water systems performances, and generates a score based on the building’s energy efficiency levels. The Passivhaus standard, developed in Germany, is one of the most stringent standards and is also the fastest growing energy performance standard in the world with more than 30,000 buildings certified to date. It also focuses on building fabric but establishes a maximum energy consumption target. In this work, the authors developed a comparative review of the RTQ-R label and the Passivhaus standard as means to inform a broader debate about building codes in the context of the current calls by governments for increased energy efficiency. The findings highlighted the different nature of the standards’ requirements and targets adopted, and the benefits and constraints of both.